Chemical hazards in pork and health risk: A review - Tran Thi Tuyet Hanh; Nguyen Thi Minh Duc; Phuc Pham Duc; Chu Van Tuat; Hung Nguyen-Viet (2015)
Pork is consumed daily at large quantities in many countries in the world and global pork consumption accounted for 36% of all meat consumed in 2007 and 75% for Viet Nam in 2013 (GSO, 2013). Currently, the issue of toxic chemicals in pork and pork products is of concern by organizations and consumers. A number of studies have documented elevated levels of chemicals found in pork and pork products, which potentially result in negative impacts on consumers' health. However, in developing countries, including Viet Nam, chemicals in pork and health risks have been given inadequate attention. There have been currently very few publications on international peer-reviewed literature and little research on the impacts of chemicals in pork on consumers' health in the country. This review summarizes data available on ScienceDirect database and Vietnamese scientific journals to synthesize information about chemical hazards in pork, pork products and related health risks. The chemical hazards mentioned in this review are mostly common toxic chemicals such as heavy metals, residues of veterinary drugs, dioxin, additives and toxic substances generated during meat processing. In addition, the review also provides recommendations for future research.